2019
DOI: 10.1016/j.heliyon.2019.e02562
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of coal fired-fly ash for potential heavy metal removal from the single and multi-contaminated system

Abstract: In this study, adsorption of three different heavy metals i.e. cadmium (Cd (II)), copper (Cu (II)) and nickel (Ni (II)) was carried out in single and multi-contaminated system using coal-fired fly ash (CFFA). Initially, for the single contaminated system, various physical process parameters were selected for optimization by deploying Box–Behnken design of experiments. Further, the evaluation of CFFA for removal of heavy metals in a multi-component system from aqueous solution was performed by employing Placket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(17 citation statements)
references
References 43 publications
0
16
0
1
Order By: Relevance
“…Many researchers have reported that algal cells and may have a very high capacity for binding with metals due to the presence of polysaccharides, proteins, or lipids on the surface of cell walls, possessing the functional groups viz. aminos, hydroxyls, carboxyls and sulfhydryl, which can act as binding sites for metals (Kumar et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that algal cells and may have a very high capacity for binding with metals due to the presence of polysaccharides, proteins, or lipids on the surface of cell walls, possessing the functional groups viz. aminos, hydroxyls, carboxyls and sulfhydryl, which can act as binding sites for metals (Kumar et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%
“…Inyinbor et al., reported a total surface area of 0.0387 m 2 g −1 and 1.8642 m 2 g −1 for adsorption of Rhodamine B dye using agricultural wastes ( Inyinbor et al., 2015 ). Gracilaria edulis has a mean pore diameter of 283.69 nm which corresponding to micropore size (>50 nm) would have been due to the pretreatment of biomass ( Hwang et al., 2018 ; Kumar et al., 2019 ). Adsorbents with such macropore sizes are rarely reported.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, depending on the type of procedure used to obtain HAp, the porosimetry parameters of HAp can be diverse (e.g., 12.5-22.9 m 2 /g [71], 26.34-86.15 m 2 /g, and 0.12-0.51 cm 3 /g) [72]. Similarly, depending on its origin, coal fly ash can also have varied parameters (e.g., 12.1 m 2 /g [73], 16.2 m 2 /g and 0.031 cm 3 /g [74], 17.4 m 2 /g [52], 35 m 2 /g and 0.042 cm 3 /g [75], and 39.3 m 2 /g and 0.171 cm 3 /g) [70].…”
Section: Physical-chemical Characteristics Of Cfa-hap Compositesmentioning
confidence: 99%
“…Due to their high free CaO content (dependent on their origin), these ashes are chemical sequestering agents for CO 2 removal [50] and can be used as mineral additives in cement pastes [51]. Fly ash is also recognized as a promising adsorbent for removing heavy metals from multi-component systems [52]. The use of waste byproducts as secondary raw materials for the production of new materials in industrial and environmental applications is an important element of sustainability and the circular economy [53].…”
Section: Introductionmentioning
confidence: 99%